Sikap Nelayan Penerima Bantuan Terhadap Program Pemberdayaan di Desa Mekong Kabupaten Kepulauan Meranti Provinsi Riau - Sylvana Capriaty Pakpahan; Zulkarnain; Viktor Amrifo (Jurusan Sosial Ekonomi Perikanan, 2020)
Research on the Attitudes of Fishermen Receiving Empowerment Assistance Program in Mekong Village, Meranti Islands Regency was carried out on 10-17 May 2019. The purpose of this study is to analyze the characteristics of beneficiary fishermen, the attitudes of recipient fishermen to aid in the Mekong Village and analyze the relationship of the characteristics of the fishermen with the attitudes of beneficiary fishermen benefiting the empowerment program in the Mekong Village by using survey methods. Data collection was carried out by distributing questionnaires using a Likert scale. Analysis of the data used in this research is descriptive qualitative and quantitative techniques.The results of this study explain the relationship between the characteristics of fishermen and the attitudes of fishermen analyzed using Rank Spearman correlation. The results of the attitudes of beneficiary fishermen towards the empowerment program in the Mekong Village were neutral (91%). The relationship of each characteristic to the overall attitude of the fishermen has a insignificant relationship, meaning that the characteristics do not affect the attitudes of the beneficiary fishermen towards the empowerment program.